Design, synthesis and biological evaluation of chromeno[3,4-b]xanthones as multifunctional agents for Alzheimer’s disease - Malafaia, Daniela; Brás, Natércia F.; Sampietro, Anna; Quintelas, Inês; Ferreira, Pedro; Melo, Lúcia; Saavedra, Joana; Martinez-Gonzalez, Loreto; Pereira, Marisa; Sarabando, Jessica; König, Leo; Cardoso, Isabel; et al. (ACS chemical neuroscience, 2025)
Alzheimer’s disease (AD) remains a complex and unmet medical challenge, requiring innovative approaches to address its multifaceted pathology. In this study, we explored chromeno[3,4-b]xanthones as a novel multifunctional scaffold, synthesized via the straightforward cyclization of their precursor, (E)-2-styrylchromones. Compounds 10 and 11q-s exhibited potent and selective cholinesterase inhibition (IC50 1.7-9.0 μM for AChE and BChE), along with significant antiamyloid activity (inhibition exceeding 50% at 50 μM). Among them, compound 11r demonstrated the most well-balanced multifunctional profile against all four AD-relevant targets. Molecular docking studies revealed key π-stacking, hydrogen bonding, and halogen interactions, which underlie the selective binding of compound 11r to AChE and BChE. Moreover, docking and molecular dynamics simulations showed that compound 11r binds strongly to the L-S-shaped β-amyloid 1-42 (Aβ42) fibril with a binding affinity of −11.3 kcal/mol, representing a structural barrier to Aβ42 elongation. Additionally, compound 11r, selected as the representative scaffold, effectively disrupted Aβ aggregation, as demonstrated by in vitro studies, transmission electron microscopy (TEM), and cellular studies. It also displayed favorable drug-like properties, including predicted blood-brain barrier (BBB) permeability and an acceptable safety profile at active doses. The calcein-AM-assay also showed that this compound is unlikely to be actively effluxed from the brain. These findings underscore the therapeutic potential of chromeno[3,4-b]xanthone as multifunctional agents for AD, broadening the chemical space of small-molecule exploration.